The Impact of Self-Efficacy, Growth Mindset, Empowerment and Training on Employees’ Innovation Capability: A Conceptual Framework - Zhao, Xiangge; Tan, Gary, Peng-Liang; Wong, Chee Hoo (INTI International University, 2020)
Under the circumstances of fierce competition brought by fast technological development, employee innovation capability as a determinant of an organization’s performance, plays a significant role in developing new products, improving quality and gaining a competitive advantage. This is a conceptual paper to study the factors that influence employees’ innovation capacities based on the analysis and knowledge obtained from relevant literature, focusing on self-efficacy, growth mindset, empowerment and training. Self-efficacy and growth mindsets are psychological factors to reflect individual differences in perceiving their innovation capabilities, while empowerment and training are organizational factors that are likely to be positively related to employees’ innovation capacity. Although the paper is narrative or descriptive in nature and non-statistical, it is conducive to inspiring a better comprehension of employees’ innovation capacity.